Prevalence of Pain Due to Musculoskeletal Disorders and its Relationship to Psychosocial Risk Factors in the Personnel of organizations in Gorgan ,2013 - Mohammad Aryaie; Danial Bagheri; Mohammad Ali Vakili; Fozieh Bakhsha; Seid Yaghub Jafari; Samane Karimi; Ali Asghar Abbasi Asfajir (Golestan University of Medical Sciences, 2015)
Background and Objective: Musculoskeletal disorders are the most common occupational complaints bringing about increased financial burden and reduced social productivity. This study aimed to determine the prevalence of musculoskeletal disorders and their relationship with psychosocial factors in the staff of organization. Material and Methods: In this cross-sectional study, 675 staff of the organizations in Gorgan where selected via cluster & stratified sampling. The instruments Nordic standard questionnaire and job content including areas of job demands, decision latitude, job nature, social interaction with managers and colleagues. We analyzed the data by independent t-test, chi-square test and logistic regression (P;le0.05). Results: Seventy-seven of participants (11.4%) suffer from neck pain, 39 (5.8%) from shoulder pain and 97 (14.4%) from back pain. Multivariate logistic regression showed a significant relationship between neck pain and the support given by supervisor and Colleagues. Respectively, Freedom of decision-making and support are the most common factors associated with shoulder and back pain. Conclusion: Based on the results, the support of supervisor & Colleagues and the freedom of decision are the risk factors associated with musculoskeletal disorders.